+0  
 
0
125
1
avatar

1) 
 

2) 
 

3)


Thanks so much! I tried...

 Aug 23, 2018
 #1
avatar+98197 
+2

1)  Note that  25^(17/x)  = ( 5^2)^( 17/x)  =  5^(34/ x)

 

25^(-2)  =  5^(48/x)  / [ 5^(26/x) * 5^(34/x)  ]

 

(5^2)^(-2)   =  5^(48/x)  /  [ 5^(60/x)]

 

5^(-4)  =  5^(48/x - 60/x)

 

5^(-4)  = 5^(-12/x)

 

We have the same bases, so we can solve for the exponents

 

-4  =  -12 /x  multiply through by x

-4x  = -12   divide both sides by -4

x  = 3

 

 

cool cool cool

 Aug 23, 2018

39 Online Users

avatar
avatar
avatar